Etching Effect On The Formation Of Silicon Nanowire Transistor Patterned By AFM Lithography. - Abdullah, A. Makarimi; Hutagalung, Sabar D.; Lockman, Zainovia (2010)
Anisotropic etching of silicon has been widely used in fabrication of MEMS devices for many years. In this work, TMAH and KOH with IPA are used to etch silicon nanowire transistor patterns.